Pengaruh kepemimpinan dan motivasi terhadap kinerja guru SMK Muhammadiyah 01 Pekanbaru - Ari Rahmadani; Nuryanti '; Rio Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study to determine and analyze the effect of partiallyleadership and motivation on teacher performance and to identify and analyze simultaneously the influence of leadership and motivation on teacher performance SMK Muhammadiyah 01 Pekanbaru.Untuk identify and analyze the variables that most significantly influence the performance of teachers of SMK Muhammadiyah 01 Pekanbaru. The population is all teachers in SMK Muhammadiyah 01 Pekanbaruthat number as many as 83 people. For sampling the study, researchers used a technique Slovin the study sample was 45 people with the sampling random method (simple random sampling). Data collection techniques in this study was through questionnaires (questionaire) and interview (interview). In this study analyzed data using descriptive method, also using multiple linear regression analysisFrom the results of this study concluded partially for leadership variablessignificantly influence employee performance at SMK Muhammadiyah 01 Pekanbaru also partially motivational variables significantly influence employee performance at SMK Muhammadiyah 01 Pekanbaru. Simultaneously, the two independent variables, namely leadership and motivational variables have a relationship with the dependent variable, namely the performance of employees at SMK Muhammadiyah 01Pekanbaru (Y), it can be proven through multiple correlation coefficient (R) of 0.945.Penelitin also diketauaai relationship of the independent variable (leadership and motivation) to employee performance at SMK Muhammadiyah 01 Pekanbaru (Y) is equal to 88.70%. Variables most significantly influence the performance of teachers of SMK Muhammadiyah 01 Pekanbaru is the motivation for most of the T value.For authors suggest that schools should pay more attention to the goodrelationship between leaders and subordinates because it is a very big connection with employee performance improvement. If teachers in carrying out daily tasks to get the problem, then the supervision of a good leader will be able to look for solutions and solving problems faced by teachers will carry out duties properly. Human resources needs to be cultivated and managed in ways that achieve efficiency and effectiveness of the organizationKey Words: performance, leadership and motivation